The effect of omega-3 fatty acids on coronary atherosclerosis quantified by coronary computed tomography angiography. Issue 3 (March 2021) - Feuchtner, Gudrun; Langer, Christian; Barbieri, Fabian; Beyer, Christoph; Dichtl, Wolfgang; Friedrich, Guy; Schgoer, Wilfried; Widmann, Gerlig; Plank, Fabian
Summary: Background & aims: Data on the effects omega-3 fatty acids on coronary artery disease (CAD) are contradictory. While a recent metanalysis could not show improved cardiovascular outcomes, anti-atherogenic mechanisms are well known. Objective: Aim was to assess the influence of Omega-3 polyunsaturated long-chain fatty acids (PUFA) supplementation on coronary atherosclerosis quantified by coronary computed tomography angiography (CTA). Methods: 106 patients (59.4y± 10.7; 50% females) with low-to-intermediate risk referred to CTA were included. 53 patients under omega 3-PUFA (docosahexaenoic acid, DHA and eicosapentaenoic acid, EPA) supplementation were retrospectively matched with 53 controls (CR) for age, gender and coronary risk profile (smoking, arterial hypertension, family history, dyslipidemia, c-LDL, Cholesterol, TG, diabetes) (1:1, propensity score) and lifestyle habits (exercise, alcohol consumption and nutrition). CTA analysis included 1) stenosis severity score >70%severe, 50–70% moderate, 25–50%mild, <25% minimal), 2) total plaque burden (segment involvement score (SIS) and mixed non-calcified plaque burden (G-score) and 3) high-risk-plaque features (Napkin-Ring-Sign, low attenuation plaque (LAP), spotty calcification<3 mm, RI>1.1). CT-Density (Hounsfield Units, HU) of plaque was quantified by CTA. Results: Prevalence of coronary atherosclerosis (any plaque: 83% vs. 90.6%, p = 0.252), >50% stenosis and stenosis severity score (p = 0.134) were not different between groups. Total and non-calcified plaque burden scores were lower in the omega-3 group (2.7 vs. 3.5, p = 0.08 and 4.5 vs. 7.4, p = 0.027 for SIS and G-score, resp.). Coronary artery calcium score (CACS) was similar (84.7 vs. 87.1AU). High-risk-plaque prevalence was lower in the Omega-3 group (3.8% vs. 32%, p < 0.001); the number of high-risk-plaques (p < 0.001) and Napkin-Ring-Sign prevalence was lower (3.8% vs. 20.9%) (p < 0.001), resp. CT-density (HU) of plaque was higher in the Omega-3 group (131.6 ± 2 vs. 62.1 ± 27, p = 0.02) indicating more fibrous-dense plaque component rather than lipid-rich atheroma. Mean duration of Omega-3 intake was 38.6 ± 52 months (range, 2–240). Conclusions: Omega-3-PUFA supplementation is associated with less coronary atherosclerotic "high-risk" plaque (lipid-rich) and lower total non-calcified plaque burden independent on cardiovascular risk factors. Our study supports direct anti-atherogenic effects of Omega-3-PUFA. Highlights: Omega-3-PUFA reduce coronary "high-risk" plaque quantified CTA. Omega-3-PUFA increase plaque density. Our study supports the beneficial effect of Omega-3-PUFA for cardiovascular event prevention.